Age-Related Differential Effects of School-Based Sitting and Movement Meditation on Creativity and Spatial Cognition: A Pilot Study - Fabio Marson; Antonio De Fano; Michele Pellegrino; Caterina Pesce; Joseph Glicksohn; Tal Dotan Ben-Soussan (MDPI AG, 2021)
Psychophysical well-being can be supported during development by the integration of extra-curricular activities in scholastic settings. These activities can be implemented in different forms, ranging from physical activities to sitting meditation practices. Considering that both such activities are thought to affect children's psychophysical development, a movement-based meditation that combines the two approaches−in the form of a short daily activity−could represent a powerful tool to promote healthy physical and mental development. Consequently, the current pilot study aimed to examine the effect of short daily school-based sitting and movement meditation trainings on creativity and spatial cognition. Utilizing a crossover design, we evaluated their feasibility and efficacy at different ages among children (n = 50) in 5th to 8th grade. We observed that 5 weeks of daily training in sitting and movement meditation techniques improved children's cognition differently. Specifically, younger children showed greater creativity and better spatial cognition following the movement-based meditation, while older children showed greater enhancement in these areas following sitting meditation training. This suggests that training can affect children's cognition differently depending on their developmental stage. We discuss these results within the framework of embodied and grounded cognition theories. Information on feasibility and age-related effect sizes derived from the current study paves the way for future well-powered larger-scale efficacy studies on different forms of school-based interventions to cognitive development promotion.